IMPLEMENTATION OF GUIDED IMAGINATION TECHNIQUES FOR REDUCES PAIN IN POST ORIF PATIENTS CRURIS DEXTRA FRACTURE - Ri'ayatul Maula, Dedeh (Akademi Keperawatan Giri Satria Husada Wonogiri, 2024)
Fractures are fractures caused by trauma or physical exertion, as well as the soft tissue around the bones that can determine whether a fracture is complete or not. The purpose of study was to determine whether the implementation of guided imagery techniques was effective in reducing the pain scale in cruris fracture postoperative patients. This research is in the form of a case study using a descriptive research method. The results of implementing guided imagery technique nursing actions for 3 days found that pain was reduced, this proves the act providing guided imagery techniques can affect the process of reducing pain intensity. On the first day the authors get data a pain scale of 5 from (0-10) to 4, on day 2 the patient's pain scale from 4 to 3, on day 3 the authors get data on a patient's pain scale from 3 to 2. The results of this case study are expected can be useful for learning media and as a scientific reference for further researchers, especially in the field of nursing. Fraktur merupakan patahnya tulang yang ditimbukan oleh adanya trauma atau kekuatan fisik, serta disebabkan oleh jaringan lunak sekitarnya yang dapat menentukan patah tulang yang terjadi lengkap atau tidak lengkap. Tujuan dari penelitian ini adalah untuk mengetahui apakah penerapan teknik imajinasi terbimbing efektif dalam mengurangi tingkat nyeri pada pasien pasca operasi fraktur. Penelitian ini berbentuk studi kasus yang menggunakan metode penelitian deskriptif. Hasil penerapan teknik imajinasi terbimbing selama 3 hari didapatkan bahwa nyeri berkurang, hal ini membuktikan bahwa tindakan pemberian teknik imajinasi terbimbing dapat mempengaruhi dalam proses penurunan intensitas nyeri. Pada hari ke 1 penulis mendapatkan data skala nyeri 5 dari (0-10) menjadi 4, pada hari ke 2 skala nyeri pasien dari 4 menjadi 3, pada hari ke 3 penulis mendapatkan data skala nyeri pasien dari 3 menjadi 2. Diharapkan hasil studi kasus penelitian ini dapat bermanfaat bagi pasien dengan nyeri dan sebagai referensi ilmiah bagi peneliti selanjutnya khususnya dibidang keperawatan.